2020
DOI: 10.1002/admt.202000829
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Printed Morphing Nozzle to Control Fiber Orientation during Composite Additive Manufacturing

Abstract: Fiber‐filled composite materials offer a unique pathway to enable new functionalities for systems built via extrusion‐based additive manufacturing (or “3D printing”); however, challenges remain in controlling the fiber orientations that govern ultimate performance. In this work, a multi‐material, shape‐changing nozzle—constructed by means of PolyJet 3D printing—is presented that allows for the spatial distribution of short fibers embedded in polymer matrices to be modulated on demand throughout extrusion‐based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Reproduced with permission. [ 78 ] Copyright 2021, WILEY‐VCH Verlag GmbH. d) Schematic illustration of cellulose fibril alignment (top left), images of stained fibrils in different processes (bottom left), and biomimetic 4D printing of the samples composed of different printing paths (right).…”
Section: Direct Ink Writingmentioning
confidence: 99%
“…Reproduced with permission. [ 78 ] Copyright 2021, WILEY‐VCH Verlag GmbH. d) Schematic illustration of cellulose fibril alignment (top left), images of stained fibrils in different processes (bottom left), and biomimetic 4D printing of the samples composed of different printing paths (right).…”
Section: Direct Ink Writingmentioning
confidence: 99%
“…The designs and protocols for additively manufacturing all of the components and systems in this work were based on the use of an Objet500 Connex3 PolyJet 3D printer (Stratasys, Eden Prairie, MN) and are similar to those reported in our previous work (57). Initially, all of the fluidic circuit elements, soft actuators, ports, and integrated soft robotic systems were modeled using the CAD software SolidWorks (Dassault Systèmes SE, France).…”
Section: Polyjet 3d Printing-based Fabricationmentioning
confidence: 99%
“…Theoretical simulations of the fluidic transistors were performed using the commercial FEA software COMSOL Multiphysics v.5.3a (COMSOL Inc., Sweden) via methods similar to those reported in our previous work (57). Initially, the complete 3D CAD model (i.e., including both materials fully assembled) corresponding to each fluidic transistor was imported into the FEA software, and then the distinct material properties were set for the compliant and rigid components.…”
Section: Fea Simulationsmentioning
confidence: 99%
“…The influence of different angles of the internal geometry of the nozzle in the convergent section before the orifice on the pressure necessary for extrusion has also been investigate in terms of fiber shortening [ 49 ]. In direct write AM a nozzle with changing orifice diameter has been reported that can influence the fiber orientation by changing from a convergent to a divergent flow [ 50 ].…”
Section: Introductionmentioning
confidence: 99%